FEEDBACK MECHANISMS IN THE EDUCATIONAL PROCESS AND THE PSYCHOLOGICAL PROBLEMS OF THEIR APPLICATION - Baylarova, Zeynab; Bagirova, Melek; Mammadhasanova, Aysun; Mammadova, Narmin (Health and Society, 2026)
This article examines the role of emotional effects in providing feedback in training. The research was conducted with the participation of 40 students. In addition to studying the psychological mechanisms for establishing feedback in training, the dynamics of various variables during feedback were also examined. During the study, it was observed that changes in students’ motivation, self-assessment, and learning achievements were higher under negative emotional influences compared to positive ones, and a negative correlation was found ($p=0.03$). This fact indicates that feedback undergoes a significant change during positive and negative emotional experiences, and the more long-term these relationships are, the more active the moderator changes become.